Excluded volume effects in the quark meson coupling model - Panda, P. K. [UNESP]; Bracco, M. E. [UNESP]; Chiapparini, M. [UNESP]; Conte, E. [UNESP]; Krein, G. [UNESP] (My University, 2002)
Excluded volume effects are incorporated in the quark-meson coupling model to take into account in a phenomenological way the hard-core repulsion of the nuclear force. The formalism employed is thermodynamically consistent and does not violate causality. The effects of the excluded volume on in-medium nucleon properties and the nuclear matter equation of state are investigated as a function of the size of the hard core. It is found that in-medium nucleon properties are not altered significantly by the excluded volume, even for large hard-core radii, and the equation of state becomes stiffer as the size of the hard core increases.